2007
DOI: 10.1090/s0025-5718-07-01965-5
|View full text |Cite
|
Sign up to set email alerts
|

A dual finite element complex on the barycentric refinement

Abstract: Abstract. Given a two dimensional oriented surface equipped with a simplicial mesh, the standard lowest order finite element spaces provide a complex X • centered on Raviart-Thomas divergence conforming vector fields. It can be seen as a realization of the simplicial cochain complex. We construct a new complex Y • of finite element spaces on the barycentric refinement of the mesh which can be seen as a realization of the simplicial chain complex on the original (unrefined) mesh, such that the L 2 duality is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(128 citation statements)
references
References 26 publications
2
126
0
Order By: Relevance
“…Two sets of functions will be used in the rest of this paper: the familiar RWG functions [2] and the Buffa-Christiansen (BC) or ChenWilton functions [4,5]. Both these sets of functions have one function per edge of the mesh.…”
Section: Integral Equation and Scat-terermentioning
confidence: 99%
See 1 more Smart Citation
“…Two sets of functions will be used in the rest of this paper: the familiar RWG functions [2] and the Buffa-Christiansen (BC) or ChenWilton functions [4,5]. Both these sets of functions have one function per edge of the mesh.…”
Section: Integral Equation and Scat-terermentioning
confidence: 99%
“…Instead of using the familiar RWG functions for the testing, this scheme uses the rotated Buffa-Christiansen or Chen-Wilton functions [4,5]. In [1], it was shown that the solution current of this so-called mixed MFIE is lowfrequency stable, which is in stark contrast with the standard MFIE.…”
Section: Introductionmentioning
confidence: 99%
“…are the EFIE operators discretized with standard RWG f [9] and BC basis functions f BC [10] respectively, Kk…”
Section: Discretization Strategymentioning
confidence: 99%
“…The above-mentioned integrals can be categorized into weakly singular (1) and (2) and strongly singular (3), respectively. Moreover, one can easily replace RWG functions with the novel Buffa-Cristiansen functions [10] without affecting the overall mathematical complexity since the latter are linear combinations of the former on the barycentric mesh. Finally, smart usage of both functions can lead to well-tested SIE operators, improving the overall accuracy of SIE solvers, provided of course that the associated impedance matrix elements are accurately computed.…”
Section: Problem Statementmentioning
confidence: 99%